The Theory of Integral Individuality by Wolf Merlin - Dorfman, Leonid (Journal of Psychology and Psychotherapy Research, 2024)
The analysis of Wolf Merlin's ideas on the integral individuality has been performed. The main problem that the theory of individuality addresses is the large number of individual traits. They vary from biochemical to socio-psychological, are heterogeneous in origin, and separated. W. S. Merlin overcomes this dominant trend by contrasting it with the assumption of human unity. This issue relates to individuality, its traits, and connections. Merlin sets out a scientific task to investigate whether individual traits can function jointly. The hypothesis was whether individual traits of diverse origins function in the form of integration. The theory put forward by Merlin allows examination of this hypothesis. It was tested by applying the concepts of levels, polymorphism, and mediation, mainly. On this basis, Merlin considered not only individual differences, but also the ways in which individual traits function together. Then, they were generalized as the theory of integral individuality. In addition, a new field of research has arisen. It has separated itself from the study of personality in general psychology and the research of individual differences in psychophysiology to some extent. The perspective advances a further study of the theory of integral individuality. Finally, the summary completes this work. Herewith, some implications and limitations are traced.